N-acetyl cysteine in the treatment of alcohol use disorder in patients with liver disease: Rationale for further research. (3rd August 2018) - Morley, Kirsten C.; Baillie, Andrew; Van Den Brink, Wim; Chitty, Kate E.; Brady, Kathleen; Back, Sudie E.; Seth, Devanshi; Sutherland, Greg; Leggio, Lorenzo; Haber, Paul S.
ABSTRACT: Introduction : Alcoholic liver disease (ALD) is the leading cause of alcohol-related death and one of the most common forms of liver disease. Abstinence from alcohol is crucial to reducing morbidity and mortality associated with the disease. However, there are few pharmacotherapies for alcohol use disorder suitable for those with significant liver disease. Areas Covered : This paper presents a rationale for investigating the use of N-acetyl cysteine (NAC) to promote abstinence or reduce heavy alcohol consumption for patients with an alcohol use disorder, particularly in the presence of liver disease. NAC is an antioxidant with glutamatergic modulating and anti-inflammatory properties. Evidence is emerging that oxidative stress, neuro-inflammation and dysregulation of glutamatergic neurotransmission play a key role in alcohol use disorder. Similarly, oxidative stress is known to contribute to ALD. We outline the studies that have investigated NAC to reduce alcohol consumption including preclinical and clinical studies. We also review the evidence for NAC in other addictions as well as psychiatric and physical comorbidities associated with alcohol use disorders. Expert Opinion : NAC is low cost, well-tolerated and could have promise for the treatment of alcohol use disorder in the presence of liver disease. Clinical trials directly examining efficacy in this population are required.